New Frontiers in Gut Nutrient Sensor Research: Luminal Glutamate-Sensing Cells in Rat Gastric Mucosa - Eiji Nakamura; Mai Hasumura; Ana San Gabriel; Hisayuki Uneyama; Kunio Torii (Elsevier, 2010)
Dietary free glutamate is known to elicit umami, one of the five basic tastes percepted via the specific taste sensor cells on the tongue. Recent studies suggest the specific glutamate sensors exist in the gastric mucosa and contribute to the regulation of gastrointestinal functions, yet the precise mechanism remains still unknown. We established the method to enrich various cell fractions from the isolated rat gastric mucosa and characterized the expression of putative glutamate sensors using such cell fractions. The gastric mucosal cell fractions such as surface mucous, parietal, chief, and endocrine cells were successfully prepared by mucosal protease digestion, elutriation, and gradient centrifugation. The characteristics of these cells were confirmed by real-time RT-PCR using the respective cell-specific markers. Parietal cell fraction exclusively expressed putative umami receptor molecules such as T1R1 and mGluR1 compared to other fractions, although the degree of expression was low. In contrast, the representative taste cell specific markers such as PLCβ2 and TRPM5 were specifically expressed in the smaller endocrine cell fraction. Both parietal and smaller endocrine cell fractions also positively expressed some mGluR subtypes. The chief-cell fraction less expressed T1R1 and mGluR1. These results suggest that multiple glutamate sensors, probably different mechanisms from taste buds, contribute to the glutamate sensing in the gastric mucosa. Keywords:: glutamate, gastric mucosa, endocrine cell, chemosensing, umami, gastrointestinal tract